2013
DOI: 10.1007/s00284-013-0481-8
|View full text |Cite
|
Sign up to set email alerts
|

Ottowia shaoguanensis sp. nov., Isolated From Coking Wastewater

Abstract: A Gram-negative, short rod-shaped, floc-forming bacterial strain J5-66(T) without any flagellum was isolated from coking wastewater collected from Shaoguan, Guangdong, China. It was capable of optimal growth at pH 7, 30 °C, and 1-2 % (w/v) NaCl. Phylogenetic analysis based on 16S rRNA gene sequences showed that this strain belonged to the genus Ottowia in Comamonadaceae, and the highest 16S rRNA gene sequence similarity was 96.2 % with Ottowia pentelensis DSM 21699(T). The major cellular fatty acids of strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 19 publications
0
15
1
Order By: Relevance
“…In the anaerobic sludge, the facultative aerobic Gram-negative bacterium Ottowia was the most abundant genus, which differed from previous studies Zhu et al 2016). Though Ottowia has been isolated from activated sludge treating CWW wastewater (Felfoldi et al 2011;Cao et al 2014;Geng et al 2014), its presence at such a high abundance in anaerobic sludge was not reported previously. The presence of Ottowia together with Advenella Ghosh et al 2011), Corynebacterium (Dalal et al 2012;Guo et al 2015), and Sphingobium (Kertesz and Kawasaki 2010) might be associated with the removal of phenols, NHCs as well as PAHs under the anaerobic conditions (Table S8).…”
Section: Discussioncontrasting
confidence: 73%
“…In the anaerobic sludge, the facultative aerobic Gram-negative bacterium Ottowia was the most abundant genus, which differed from previous studies Zhu et al 2016). Though Ottowia has been isolated from activated sludge treating CWW wastewater (Felfoldi et al 2011;Cao et al 2014;Geng et al 2014), its presence at such a high abundance in anaerobic sludge was not reported previously. The presence of Ottowia together with Advenella Ghosh et al 2011), Corynebacterium (Dalal et al 2012;Guo et al 2015), and Sphingobium (Kertesz and Kawasaki 2010) might be associated with the removal of phenols, NHCs as well as PAHs under the anaerobic conditions (Table S8).…”
Section: Discussioncontrasting
confidence: 73%
“…It was not detected in any background technical controls. Ottowia is a genus of bacteria that has been isolated from industrial and municipal wastewater (96)(97)(98)(99), sikhye (100), tofu residue (101), and fish intestines (102); it has not been identified in investigations of the human uterus. Nevertheless, Ottowia is a member of the family Comamonadaceae, and Chen et al ( 23) and Winters et al (30) reported that Comamonadaceae were among the most relatively abundant bacterial taxa in the human endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…They were isolated from diverse environments including soil, freshwater, groundwater, marine environments, swamps, sewage, activated sludge, plant rhizospheres, nitrifying inocula, chickens, saline pond, and lake sediment [7,10,36,37]. During the investigation into the diversity of phenol-degrading bacteria in a coking wastewater [8], a strain designed as J5-3 T was isolated and identified. Based on the physiological, biochemical, and phylogenetic analyses, strain J5-3 T represents a novel genus belonging to the family Hyphomicrobiaceae.…”
Section: Introductionmentioning
confidence: 99%